Social background and citizen–legislator congruence in candidate-centred systems. Issue 3 (2nd July 2016) - Courtney, Michael
ABSTRACT: Legislatures are arenas where diverse policy preferences are honed into practical policy proposals. Given that legislative membership is a result of free democratic elections, there is an assumption that the attitudes and opinions of MPs are representative of the population as a whole. Thus, pre-legislative bargaining is founded on an unbiased sample of public opinion. However, considerable opinion incongruence exists between citizens and the political elite in many systems, potentially undermining this ideal democratic starting point for legislative business. Candidate-centred voting systems offer the potential to remedy this disconnect. While citizens tend to emphasise personal characteristics as an explanation for vote choice in one of the most candidate-centred systems in existence, proportional representation-single transferable vote, the disconnect of opinion congruence between citizens and elites persists. This paper finds that citizens' emphasis on MPs' personal characteristics when choosing representatives causes significant opinion congruence between citizens and elites on a demographic basis, particularly for under-represented groups such as women, younger citizens and those from lower socio-economic backgrounds, but aggregate congruence is undermined by the lack of demographic diversity among MPs.